PENGARUH MULTIPLE LARGE SHAREHOLDER STRUCTURE, LEVERAGE, DAN INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN JASA NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nita Yulistiani (Universitas Multimedia Nusantara, 2021)
Abstract— This research is quantitative and examined the effect of multiple large shareholder structure, leverage, and intellectual capital on company performance using the ROE. The data is retrieved from financial statements of service companies, exclude the finance subsector, listed on the Indonesian Stock Exchange for the period 2014-2018. There are 36 companies and 171 data for the sample using the purposive sampling method. The method of analysis used is multiple linear regression. The result is that multiple large shareholder structure, leverage, and intellectual capital have significant effects simultaneously on non-finance company performance. Partially, multiple large shareholder structure, leverage, and intellectual capital have positive and significant effects on company performance. This research proves that company performance can be enhanced by maximizing multiple large shareholder structure roles as supervisors to decrease internal conflicts and represent the minority shareholders, keeping the leverage ratio to avoid default risk, and utilizing intellectual capital to advance the value-added of the company. Keywords: Multiple Large Shareholder Structure; Leverage; Intellectual Capital; Company Performance